Characterisation of the Goods and Services Sectors: technology management implications. (14th April 2009) - Berg, Daniel; Einspruch, Norman G.
Using a technique called 'Data Surface Mining' (DSM), data previously published in the business press were further analysed to characterise the similarities and differences between the Goods and Services Sectors; a summary of the results of these analyses is presented here. In addition, the issues of technology management especially relevant to the Services Sector are presented. These issues are of critical importance in light of the fact that the Services Sector represents more than 80% (GDP and/or employment) of the US economy and is of increasing importance in the global economy.